Advancing Visual Health Communication Research to Improve Infodemic Response. Issue 14 (5th December 2020) - King, Andy J.; Lazard, Allison J.
ABSTRACT: During public health crises like the ongoing novel coronavirus pandemic, there is a need to amplify and improve critical health communication messages. This need is due to pandemics producing infodemic conditions, meaning the public information environment is oversaturated with information of questionable accuracy and utility. The strategic use of visuals can be leveraged to improve the quality of health communication during public health crises and lessen the unintended effects of infodemic conditions. In this essay, we review previous visual communication theorizing and research that provide insights for effective and efficient use of graphical (e.g., data visualizations) and illustrative (e.g., photos, illustrations, and content features) visuals. We also discuss and advocate for more systematic research on visual misinformation and visual narratives, as there are significant gaps in the literature about how people interpret, act on, and engage with these visual content types. More systematic research about these areas of visual health communication research will improve public communication during future public health crises.